Retinopathy of prematurity: results from 10 years in a single neonatal intensive care unit - Inês Coutinho; Catarina Pedrosa; Mafalda Mota; Sofia Azeredo-Lopes; Cristina Santos; Graça Pires; Susana Teixeira; Manuel Cunha (Hygeia Press di Corridori Marinella, 2017)
Introduction: Retinopathy of prematurity (ROP) is a vasoproliferative disorder of the retina of preterm newborns and is an important and preventable cause of visual impairment in childhood. This study aimed to assess the incidence and main risk factors associated with the development of ROP in the last 10 years at Hospital Prof. Doutor Fernando Fonseca in Lisbon, Portugal. Methods: Observational and retrospective study conducted between 2005 and 2014 at Hospital Prof. Doctor Fernando Fonseca. The study included newborns of gestational age < 32 weeks. We analyzed maternal, prenatal and neonatal factors associated with the development of ROP. Statistical analysis were performed with Statistical Package for Social Sciences (SPSS®) software. Univariate and multivariate analyses were performed and a multiple logistic regression model was carried out with a significance level α = 0.05. Results: 527 premature infants with a gestational age < 32 weeks were studied, of which 165 developed ROP. 60 of these patients needed treatment. In the univariate analysis, the risk factors for the development of ROP were maternal infection in pregnancy, low birth weight, low gestational age, low Apgar score at 5 minutes, need for oxygen therapy until the 28th day of life, a high score on the CRIB and SNAPPE2 scales, use of surfactant, respiratory distress syndrome, persistence of patent ductus arteriosus, peri-intraventricular hemorrhage and neonatal sepsis. In the multiple logistic regression analysis, risk factors for ROP were the presence of neonatal sepsis, respiratory distress syndrome, persistence of patent ductus arteriosus and a high score on the neonatal SNAPPE2 scale. Conclusions: We found a ROP incidence rate of 31.3%, with risk factors similar to those observed in other studies.